Pengaruh Budaya Organisasi Kepemimpinan dan Lingkungan terhadap Kepuasan Kerja Karyawan pada UD Suwarlandono Art Di Tanggulangin - Ayu Faiza Rochmah; Bowo Santoso; Endang Iriyanti (Syntax Idea, 2021)
In terms of employees who work, job satisfaction is an important factor to note. An individual will feel satisfied at work if the aspects of the job and himself are supportive. Job satisfaction is formed from several aspects, including organizational culture, leadership, anddworkkenvironment..On theebasis offthissthought, thissstudy aims toodeterminexthexinfluence ofxOrganizational Culture, Leadership,.and.Work EnvironmentxonxEmployeexJob Satisfaction at UD. Suwarlandono Art at Tanggulangin. This.studyyusesxprimaryxdataxobtained fromxrespondents'.answers withxaxsample ofx60 employees in the production department. Data analysis techniques using PartialxLeastxSquare. The.resultsxofxthexstudy canxbexconcluded thatxOrganizational Culture, Leadership, andxWorkxEnvironment have.a.positive and significant.influence on.EmployeexJobxSatisfaction.